Demographics, Mechanisms of Injury, and Concurrent Injuries Associated With Calcaneus Fractures: A Study of 14 516 Patients in the American College of Surgeons National Trauma Data Bank. Issue 5 (October 2017) - Bohl, Daniel D.; Ondeck, Nathaniel T.; Samuel, Andre M.; Diaz-Collado, Pablo J.; Nelson, Stephen J.; Basques, Bryce A.; Leslie, Michael P.; Grauer, Jonathan N.
Background . This study uses the American College of Surgeons National Trauma Data Bank (NTDB) to update the field on the demographics, injury mechanisms, and concurrent injuries among a national sample of patients admitted to the hospital department with calcaneus fractures. Methods . Patients with calcaneus fractures in the NTDB during 2011-2012 were identified and assessed. Results . A total of 14 516 patients with calcaneus fractures were included. The most common comorbidity was hypertension (18%), and more than 90% of fractures occurred via traffic accident (49%) or fall (43%). A total of 11 137 patients had concurrent injuries. Associated lower extremity fractures had the highest incidence and occurred in 61% of patients (of which the most common were other foot and ankle fractures). Concurrent spine fractures occurred in 23% of patients (of which the most common were lumbar spine fractures). Concurrent nonorthopaedic injuries included head injuries in 18% of patients and thoracic organ injuries in 15% of patients. Conclusion . This national sample indicates that associated injuries occur in more than three quarters calcaneus fracture patients. The most common associated fractures are in close proximity to the calcaneus. Although the well-defined association of calcaneus fractures with lumbar spine fractures was identified, the data presented highlight additional strong associations of calcaneus fractures with other orthopaedic and nonorthopaedic injuries. Levels of Evidence: Prognostic, Level III: Retrospective review of a prospectively collected cohort